Psychoreligious Therapy in Paranoid Schizophrenia with Comorbid Hyperthyroid - Agelia Rizky Jayanti; Arum Pratiwi; Slamet Wibowo (GLOBAL HEALTH SCIENCE GROUP, 2026)
Schizophrenia is a chronic mental disorder characterized by delusions, a symptom of which is a disturbance in the patient's thought processes that impacts the patient's behavior. The purpose of this study was to describe a case of a schizophrenic patient with delusions as the primary symptom and comorbid hyperthyroidism who was given psychoreligious therapy. This qualitative case study involved a single patient diagnosed with paranoid schizophrenia and comorbid hyperthyroidism, selected using purposive sampling. Data were collected through interviews, behavioral observations, physical examinations, and laboratory data. Management included pharmacological therapy in the form of antipsychotics and hyperthyroid medications, and non-pharmacological interventions in the form of reality orientation and psychoreligious therapy. The results of the therapy were obtained through daily observations, interviews, and assessment of reality orientation and behavioral responses, and were analyzed descriptively by comparing the patient’s condition before and after the intervention. The findings showed a decrease in the intensity of delusions, stabilization of thought patterns, and improvement in the patient’s behavioral functioning, including an increased ability to distinguish reality and more regular religious activities. The conclusion of this study is that hyperthyroidism is suspected to trigger symptoms of anxiety and physical complaints such as heart palpitations and abdominal pain due to irregular eating patterns. A holistic approach combining medical and psychosocial therapy was effective in managing schizophrenic symptoms and comorbid conditions, as well as improving the patient's quality of life.